Schulze and Brand type a-IV dens invaginatus with radicular cyst: A rare case report - Rachita Chengappa; Asim Mustafa Khan; Kavitha Puttaswamy; Paul James Kolathingal (Wolters Kluwer Medknow Publications, 2015)
Though a clinical examination may reveal a deep fissure or pit on the surface of an anterior tooth, radiographic examination is a more accurate approach to diagnose an invagination. Dens invaginatus is one of the common dental deformities, but the defect involving the root and its association with radicular cyst is still very uncommon. The objective of this case presentation is to report a case of radicular dens in dente, which is a rare dental anomaly. This case report shows that dens invaginatus with an open apex and a radicular cyst can be treated successfully using currently available materials.